(untitled) (Research, Society and Development, 2021)
The food ecology of a given species is part of and directly interferes in the dynamics of its population, becoming relevant for the conservation of the ecosystem. Thus, this study allowed the study of the main aspects of trophic ecology, in addition to the feeding strategy and possible ontogenetic variations in the feeding of the Centropomus undecimalis sea bass in the municipality of Tutóia - MA. The methodology used consisted of identifying and removing biometric data and dissecting 147 stomachs for analysis of stomach contents, using a stereoscopic microscope. In addition, the classification of the digestion stages was carried out, based on the repletion index and degree of digestion, as well as the identification of food items at the lowest possible taxonomic level. As main results, it was possible to characterize through the analysis of Frequency of Occurrence (Fo), Volumetric Frequency (Fv) and Food Importance Index (IAi) that the item fish with 79% prevailed in the diet of the species, followed by crustaceans, shrimp 21%. As to the degree of fullness, all categories were representative, with empty stomachs and little food (1/2) being the most frequent. As for the degree of digestion, the digested category had greater predominance among the others. Thus, according to the stomach analyses, it can be inferred that the species is a general opportunistic predator since it does not feed only on fish and has a carnivorous behavior with a dominant feeding strategy for piscivores.